Servant Leadership and Governance Practices in Catholic Schools: A Quantitative Study of Their Influence on College Students (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This quantitative study examined the influence of servant leadership and mission-aligned governance practices on student formation in Catholic higher education institutions. College students enrolled in selected Catholic colleges participated in the study through a structured survey questionnaire measuring servant leadership practices, mission-aligned governance practices, and student formation in terms of academic motivation, engagement, and values development.Descriptive statistics were used to determine the level of leadership and governance practices, while correlation and regression analyses examined their predictive influence on student formation. Results indicated that servant leadership and mission-aligned governance were perceived at very high levels and significantly predicted student formation outcomes. The findings emphasize the importance of value-centered leadership and mission-driven governance in strengthening the formative mission of Catholic education. The study provides empirical evidence that may guide institutional leaders and policymakers in enhancing leadership development and governance practices within Catholic higher education.